JARING PATRIARKI: CERPEN JARING-JARING MERAH KARYA HELVY TIANA ROSA MELALUI FEMININE MYSTIQUE BETTY FRIEDAN - Ridho Sastro Panjaitan; Tabita Tesalonika Simaremare; Grace Evelyn Hutabarat; Irfansyah Barus; Jakaria Jakaria (STKIP Subang, 2026)
This study analyzes the depiction of patriarchy in Helvy Tiana Rosa's short story